Synthesis, characterization and band gap studies of ƞ-Al₂O₃, ƞ-Al₁.₉Fe₀.₁O₃ and ƞ-Al₁.₉Ni₀.₁O₃ nanostructured materials obtained via selfpropagating combustion (SPC) method / Mawar Hazwani Jasimin - Jasimin, Mawar Hazwani (2015)
ƞ-Al₂O₃ is one of the metastable phases of aluminum oxide and known to be a very important support material for heterogeneous catalysts used extensively in the chemical industry. This phase is not easy to obtain. In this research, the ƞ-phase is synthesized using a novel method, the self-propagating combustion (SPC) and the properties of ƞ-Al₂O₃ and doped ƞ-Al₂O₃ nanostructured materials were investigated. The synthesis parameters are optimized to obtain pure and single phase ƞ-Al₂O₃, ƞ-Al₁.₉Fe₀.₁O₃ and ƞ-Al₁.₉Ni₀.₁O₃ nanomaterials. Materials characteristics inclusive of thermal behaviour, phase, stoichiometry structure, morphology and crystallite size were studied. Results showed that the substitution of Al with other metals (Ni, Fe) without changing the crystal structure affects the characteristics of material as well as their band energies.In this study, the effect of temperature on the phase formation of ƞ-Al₂O₃, ƞ-Al₁.₉Fe₀.₁O₃ and ƞ-Al₁.₉Ni₀.₁O₃ were investigated. It was found that the annealing temperature has to be optimized to obtain pure ƞ-phase…